1998
DOI: 10.1084/jem.188.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Proinflammatory Responses by Ligating the Macrophage Fcγ Receptor Type I

Abstract: Macrophages can respond to a variety of infectious and/or inflammatory stimuli by secreting an array of proinflammatory cytokines, the overproduction of which can result in shock or even death. In this report, we demonstrate that ligation of macrophage Fcγ receptors (FcγR) can lead to a reversal of macrophage proinflammatory responses by inducing an upregulation of interleukin (IL)-10, with a reciprocal inhibition of IL-12 production. IL-10 upregulation was specific to FcγR ligation, since the ligation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
244
1
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(275 citation statements)
references
References 23 publications
27
244
1
3
Order By: Relevance
“…IL-10 production was increased from 342 Ϯ 10 to 696 Ϯ 203 pg/ml in the presence of apoptotic neutrophils and further increased to 1101 Ϯ 203 pg/ml in the presence of opsonized neutrophils (Table II). This up-regulation of IL-10 by opsonized cells is consistent with published data (22,31). These data collectively demonstrate that the induction of reduced proinflammatory cytokine production by monocytes coupled with the promotion of augmented IL-10 production are specific to apoptotic neutrophils.…”
Section: The Effect On Cytokine Production Is Specific To Apoptotic Nsupporting
confidence: 91%
See 1 more Smart Citation
“…IL-10 production was increased from 342 Ϯ 10 to 696 Ϯ 203 pg/ml in the presence of apoptotic neutrophils and further increased to 1101 Ϯ 203 pg/ml in the presence of opsonized neutrophils (Table II). This up-regulation of IL-10 by opsonized cells is consistent with published data (22,31). These data collectively demonstrate that the induction of reduced proinflammatory cytokine production by monocytes coupled with the promotion of augmented IL-10 production are specific to apoptotic neutrophils.…”
Section: The Effect On Cytokine Production Is Specific To Apoptotic Nsupporting
confidence: 91%
“…Similarly, in the presence of opsonized apoptotic neutrophils, which would trigger the CD16 receptor, we show that LPS stimulation drives a proinflammatory response. This is a previously reported phenomenon of CD16 ligation (22,31). This is the first report to define the interaction between apoptotic neutrophils and blood monocytes.…”
Section: Discussionsupporting
confidence: 66%
“…Densitometric quantitation of three separate RNase protection assays indicated that whereas IL-12 mRNA levels decreased by Ͼ90%, the mRNA levels for MIF, IL-6, and IL-1RA were not significantly diminished following Fc␥R ligation. A single other gene, IL-10, was increased following Fc␥R ligation, as previously reported (37). The addition of control unopsonized erythrocytes, which do not bind to specific macrophage receptors, did not affect cytokine mRNA production.…”
Section: Il-12 P40 and P35 Gene Transcription Are Selectively Inhibitsupporting
confidence: 62%
“…LPS from Escherichia coli 0127:B8 was purchased from Sigma (St. Louis, MO). IgG-opsonized erythrocytes (EIgG) were generated by incubating sheep erythrocytes (Lampire, Pipersville, PA) with rabbit anti-sheep erythrocyte IgG (Cappel, Durham, NC) at nonagglutinating titers for 40 min at room temperature, as previously described (37). EIgG were washed with HBSS (Life Technologies, Grand Island, NY) and resuspended at 2 ϫ 10 8 cells/ml and used the same day.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…'Regulatory' macrophages can secrete large amounts of interleukin-10 (IL-10) in response to Fc receptor-γ ligation [11,12]. In contrast to pro-inflammatory and anti-microbial M1 macrophage responses, M2 macrophages exhibit potent anti-inflammatory activity and have important roles in wound healing and fibrosis [13,14].…”
Section: Introductionmentioning
confidence: 99%